Kynurenic acid protects against mastitis in mice by ameliorating inflammatory responses and enhancing blood-milk barrier integrity. (September 2021) - Zhao, Caijun; Wu, Keyi; Bao, Lijuan; Chen, Luotong; Feng, Lianjun; Liu, Zhuoyu; Wang, Ying; Fu, Yunhe; Zhang, Naisheng; Hu, Xiaoyu
Highlights: Kynurenic acid (KYNA) alleviates LPS-induced mastitis in mice. KYNA improves the integrity of blood-milk barrier and limits pro-inflammatory cytokines expression in vivo and in vitro. KYNA inhibits NF-κB and activates of Nrf2/Ho-1 signaling pathways. The inhibition of KYNA on LPS-induced inflammation is mediated by GPR35. KYNA ameliorates S. aureus and E. coli induced mastitis in mice. Abstract: Mastitis is one of the most serious diseases in humans and animals, especially in the modern dairy industry. Seeking safe and effective mastitis prevention strategies is urgent since food safety and drug residues in milk remain an enormous concern, despite the contribution of antibiotics to control mastitis. Kynurenic acid (KYNA), derived from the kynurenine pathway of tryptophan metabolism, has been shown to exhibit anti-inflammatory and immunomodulatory effects in many diseases. Recently, it was reported that impaired KYNA levels were associated with mastitis. However, the physiological role of KYNA in mastitis has not yet been elucidated. Therefore, the aim of this study was to investigate the protective role of KYNA in pathogen-induced mastitis in mice, as well as the underlying mechanism of this effect. We first evaluated the effects of KYNA on LPS-induced mastitis in mice. Additionally, the underlying anti-inflammatory mechanism of KYNA was investigated in mammary epithelial cells (MMECs). Furthermore, we examined the effects of KYNA on S. aureus and E. coli induced mastitis in mice. Our results demonstrated that KYNA alleviated LPS-induced mastitis by reducing inflammatory responses and enhancing blood-milk barrier integrity. The fundamental mechanisms involved the inhibition of NF-κB and activation of Nrf2/Ho-1, which is probably mediated by G protein-coupled receptor 35 but not aryl hydrocarbon receptor. Notably, KYNA also protected against S. aureus and E. coli induced mastitis in mice. In conclusion, our results highlight the role of KYNA in mastitis and serve as a basis for using endogenous metabolite as a novel preventative or therapeutic strategy for disease intervention.